APPLICATION OF FUZZY SUGENO METHOD FOR NUTRITION MANAGEMENT IN PATIENTS WITH DIABETES MELLITUS BASED ON WEBSITE - Alfinaty, Nurma; Maulita, Yani; Saripurna, Darjat (Yayasan Bina Internusa Mabarindo, 2024)
People's lifestyles have changed, this change is more or less influenced by the increase in people's welfare levels, which in fact has changed the type of food intake favored by the community (Sahi, 2020). Some people, especially urban people who are busy working, rarely cook themselves to meet the family's daily food needs, instead they rely on their food menu from buying ready-to-eat food from stalls or restaurants in large numbers. From habits like this people tend to choose janis food that offers the power of taste derived from fatty foods, chemical cooking spices from the factory, how to cook fried or grilled and provided a variety of flavors of chili sauce also with chemical spices factory with a variety of flavors. Diabetes Mellitus is a non-communicable disease caused by the pancreas does not produce enough insulin or the body can not process insulin that has been produced effectively. To reduce the risk of complications, blood sugar levels in patients with some of the families in the community even rarely consume vegetables, so many of their children no longer want to eat vegetables because they are not accustomed to eating vegetables in their families, which is actually a very beneficial vegetable for the body. From that background and to help patients with diabetes mellitus, the author wants to design a system or application that can control the food to be eaten, namely by choosing foods that are suitable for patients with the disease. The selection of these foods, will be assessed in accordance with the nutrients contained in the food to be consumed.